Hubungan Tingkat Penggunaan Internet dalam Mengakses Website USM (www.usm.ac.id) Terhadap Pemenuhan Kebutuhan Informasi Pada Mahasiswa FTIK USM - Yustitia, Senja; Julianto, Edi Nurwahyu; Latief, Muhammad Chaerul (Jurnal The Messenger, 2011)
Internet growing so rapidly. Information become cheap and free. Internet is now widely used a number of institutions to publicize the various activities. This step is also done by the University of Semarang (www.usm.ac.id). This website which is expected to be a center of information that can be accessed by students and public. The hypothesis of this study was: There is a relationship between the use of USM website (www.usm.ac.id) with information needs of Faculty of Information Technology and Communications USM student. This type of research is explanatory research. The result, that there is a relationship between the use of the USM website with information of FTIK USM student needs. This research also answers that there is a relationship between the use of the website with information on FTIK USM student needs.